What Is Perception?: Interpreting “Flesh, Chiasm (L'entrelacs-Le Chiasme) According To Maurice Merleau-Ponty - Paulus Eko Kristianto (Jurnal Filsafat "WISDOM", 2023)
The study of the body and chiasm according to Merleau-Ponty is an interesting subject that deserves to be explored. This is because it touches the "visible" and "invisible" areas, which are often interpreted ambiguously when dealing with bodily functions. The ambiguity that often arises is that the two are not used together or one is chosen. Even if together, it is usually seen as a support or a complement. In fact, the two are inseparable and interrelated. Through literature research, the author tries to show key descriptions related to the area by overseeing the perception frame. The results show that the "visible" can be likened to the skin and surface, while the "unseen" is the flesh beneath. For Merleau-Ponty, it does not mean "the invisible" supports "the visible". The integration between the "visible" and "invisible" can be said as a chiasm. A chiasm is a criss-cross framework. This idea is not easily accepted by feminist philosophers. Merleau-Ponty seems to understand that the inherent flesh with the chiasm of subjects and the world is the embodiment of a new ontology. This ontology focuses on between life and death, animals and humans, which seem hierarchical, so it attracts the attention of feminists, at least represented by Irigaray. Irigaray believes that the "visible" privilege of touch contributes to phallogocentrism because the penis is judged to be "the visible", while the vagina is the opposite, "the invisible".